Faktor-Faktor yang Menentukan Kepuasan Kerja Pegawai - Kurniawan, Muhammad; Hendri, Edduar (Jurnal Ekonomi Modernisasi, 2017)
The purpose of this study is to determine the factors that affect job satisfaction of employees in regionally owned enterprise. Based on the background to the problem, earlier theories and researches, these factors are work environment, organizational culture and work motivation . The study was conducted at the Prodexim Regional Company of South Sulawesi. Used of 70 people as respondents. The analysis technique used is path analysis. The result of the research shows that the work environment and organizational culture has a positive effect on work motivation and job satisfaction, but motivation has no effect on job satisfaction in regionally owned enterprise of Prodexim South Sumatera. Motivation cannot role as mediation variable between work environment and organizational culture toward job satisfaction. Implication of the research that increasing employee satisfaction can be improvement through work environment and organizational culture.